Pengaruh Variabel Sosial Ekonomi Terhadap Perkawinan Usia Anak pada Wanita di Indonesia Tahun 2017 - Ade Widiantara; Risni Julaeni Yuhan (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2019)
Child marriage in Indonesia is currently at an alarming condition. It is known that there are 20 provinces with child marriage pravain rates above the national figure in 2015. The deprivation of the basic rights of girls who are married before the age of 15-18 years has an impact on increasing maternal mortality, infant mortality rate, giving birth to malnourished infants, stairs such as quarrels, arguments, prolonged conflicts, leading to divorce. In addition, the problem will certainly lead to high dependency ratio. In an effort to suppress marriage issues of childhood, it becomes important to know the socioeconomic factors affecting the first marriage age for women who marry the age of the child. Therefore in this study will be studied about the tendency of social and economic variables that affect the marriage of children aged in married women aged 15-24 years in Indonesia by using binary logistic regression analysis. The results showed that 1 in 4 women ever married 15-24 years of marriage at the age of the child. Based on the result of logistic regression analysis that is domicile domicile of residence, work status and type of work of woman, level of education of woman, parent education level, age of first marriage of parent and poverty status have significant effect to the marriage of child to woman ever married age 15-24 year in Indonesia in 2017.